Functional characterization of tumor necrosis factor receptor-associated factor 3 of sea perch (Lateolabrax japonicas) in innate immune. Issue 75 (April 2018) - Zhang, Wanwan; Jia, Peng; Liu, Wei; Li, Yunlong; Yi, Meisheng; Jia, Kuntong
Abstract: Tumor necrosis factor receptor-associated factor 3 (TRAF3) is a multifunctional regulator implicated in both bacterial defense and antiviral immunity. Here, a TRAF3 gene from the seawater fish sea perch, designated as LjTRAF3, was characterized. The full-length cDNA of LjTRAF3 was 2972 bp including a 5′ untranslated region (UTR) of 243 bp, a 3′UTR of 941 bp and a putative open reading frame of 1608 bp encoding a putative protein of 536 amino acid. The deduced LjTRAF3 protein contained a RING finger, two zinc fingers, a coiled-coil, and a meprin and TRAF-C homology domain. Phylogenetic analysis showed that LjTRAF3 shared the closest genetic relationship with Larimichthys crocea TRAF3. Gene expression analyses suggested that LjTRAF3 mRNA was ubiquitously expressed in all the tissues tested, and was up-regulated post red spotted grouper nervous necrosis virus (RGNNV) infection in vivo and in vitro . Reporter gene assay showed that LjTRAF3 significantly activated zebrafish type I interferon (IFN) promoter in vitro . During RGNNV infection, ectopic expression of LjTRAF3 significantly reduced the RNA dependent RNA polymerase transcription of RGNNV, and enhanced the expression of RIG-I-like receptors (RLR), janus kinase-signal transducers and activators of transcription (JAK-STAT) signaling pathway related genes and IFN stimulated genes (ISGs), including ISG15, PKR, VIG and TRIM39. Taken together, our results suggested that LjTRAF3 might trigger the expression of various ISGs to counter RGNNV infection by regulating the RLR-induced IFN and JAK-STAT signaling pathways. Highlights: Overexpression of LjTRAF3 suppressed RGNNV replication. Overexpression of LjTRAF3 enhanced the expressiong of RLR signaling pathway genes. Overexpression of LjTRAF3 induced the expression of IFN inducible genes. LjTRAF3 might exert anti-RGNNV activities by regulating RLR-induced IFN signaling.